A Study on the Periodic Rule of Reduction Potentials of Lanthanides on Liquid Zinc Electrode. Issue 13 (1st January 2019) - Wang, Pu; Ji, Debin; Zhang, Milin; Yan, Yongde; Han, Wei; Du, Shiyu
Abstract : In this work, the electrochemical behaviors of lanthanides (Lns) ions on the liquid zinc electrode in LiCl-KCl eutectic melt were investigated at 800 K. The result from semi-integral analysis of the cyclic voltammogram indicated that the reduction process of Ln(III) ions on the liquid zinc electrode correspond to a soluble-soluble electrochemical exchange. The potential values at which the Ln(III) ions begin to reduce on the liquid zinc electrode obtained from the cyclic voltammetry (CV) present a significant "bimodal effect". By using multiple linear regression analysis with atomic radius difference and electronegativity difference as inputs, a new periodic rule for the reduction potentials of Lns on the liquid zinc electrode was found and an empirical formula was established. The calculated and experimentally measured reduction potential values are highly consistent with each other. Moreover, this formula can be extrapolated to the thorium element.